2019
DOI: 10.1097/ogx.0000000000000680
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Posttraumatic Stress Disorder: A Review of Risk Factors, Diagnosis, and Treatment

Abstract: Importance Perinatal posttraumatic stress disorder (P-PTSD) occurs in approximately 3% to 15% of women in the postpartum period. It is often underrecognized, poorly characterized, and undertreated. If untreated, it can lead to maternal and infant morbidity. Objective The aim of this review article is to discuss P-PTSD as it relates to the obstetrician gynecologist, focusing specifically on identifying perinatal risk factors, P-PTSD diagnostic tools, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Some such factors include: history of and current mental health disorders and/or trauma, parity, fear of childbirth, pregnancy health complications and loss, subjective labor experiences, type of birth, lack of support during birth [ [4] , [5] , [6] , [7] ]. Clinically, PTSD-FC is not distinguished in the Diagnostic and Statistical Manual of Mental Disorders 5 th Edition (DSM-5) from PTSD, so clinicians must evaluate presenting symptoms and operationalize the disorder in the context of the perinatal period [ 11 ]. Prevalence rates can be difficult to detect in part from a lack of consensus of the “perinatal” timeframe as well as a lack of screening protocols; nevertheless, meta-analyses have demonstrated PTSD-FC to affect approximately 3–4% of women [ 1 , 4 , 6 , 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some such factors include: history of and current mental health disorders and/or trauma, parity, fear of childbirth, pregnancy health complications and loss, subjective labor experiences, type of birth, lack of support during birth [ [4] , [5] , [6] , [7] ]. Clinically, PTSD-FC is not distinguished in the Diagnostic and Statistical Manual of Mental Disorders 5 th Edition (DSM-5) from PTSD, so clinicians must evaluate presenting symptoms and operationalize the disorder in the context of the perinatal period [ 11 ]. Prevalence rates can be difficult to detect in part from a lack of consensus of the “perinatal” timeframe as well as a lack of screening protocols; nevertheless, meta-analyses have demonstrated PTSD-FC to affect approximately 3–4% of women [ 1 , 4 , 6 , 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified multiple sources of PTSD, such as age, sex, job title, social support, exposure intensity and psychological factors (Shrestha, 2015;Šagud et al, 2017;Cirino and Knapp, 2019;Wang Y. X. et al, 2020). Occupation may be a factor in the prevalence of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal PTSD (P-PTSD) is operationalized as a disorder occurring following a traumatic experience that lasts at least one month and occurs during pregnancy or throughout the postpartum period (Cirino & Knapp, 2019). The DSM–5 does not distinguish between PTSD and P-PTSD, so clinicians must evaluate presenting perinatal symptoms based on general PTSD guidelines.…”
Section: P-ptsd Symptom Presentationmentioning
confidence: 99%